2016
DOI: 10.1177/1052562916647984
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization at a Distance

Abstract: This paper explores how part-time students in an online international management course perceived various features of the course learning design and whether international perspectives were built into their learning experiences. The focus of the study was on cross-cultural differences across groups of learners in the United Kingdom, in other European countries and in Russia and studying the course in different languages. Using a mixed method approach, the study's results challenge the distinction between "inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 70 publications
(85 reference statements)
1
5
0
1
Order By: Relevance
“…Given the wealth of studies supporting the need and value of cross-cultural competence in management education (Allen & Young, 1997;Groves et al, 2015;Montgomery, 2009;Ng et al, 2009, Van Dyne et al, 2012, the combination of virtual and cross-cultural learning experiences is of particular importance in our current global society. These findings point to the importance of research to better understand the significance that culture has on virtual team dynamics (Alstete & Beutell, 2004;Ramanau, 2016). Taken together, these studies support the notion that student cross-cultural team projects are important learning tools, and that assessment of their effectiveness is worthy of study.…”
Section: The Importance Of Virtual Cross-cultural Teams In Management Educationsupporting
confidence: 57%
See 3 more Smart Citations
“…Given the wealth of studies supporting the need and value of cross-cultural competence in management education (Allen & Young, 1997;Groves et al, 2015;Montgomery, 2009;Ng et al, 2009, Van Dyne et al, 2012, the combination of virtual and cross-cultural learning experiences is of particular importance in our current global society. These findings point to the importance of research to better understand the significance that culture has on virtual team dynamics (Alstete & Beutell, 2004;Ramanau, 2016). Taken together, these studies support the notion that student cross-cultural team projects are important learning tools, and that assessment of their effectiveness is worthy of study.…”
Section: The Importance Of Virtual Cross-cultural Teams In Management Educationsupporting
confidence: 57%
“…Scholars have consistently advocated for virtual education experiences in university management programs (Alavi et al, 1997;Alstete & Beutell, 2004;Duus & Cooray, 2014;Ramanau, 2016;Schwartzman, 2006;Wang & Haggerty, 2011). The ability to collaborate virtually is a necessary skill for increasing virtual competence (Hertel et al, 2006;Humes & Reilly, 2008).…”
Section: The Importance Of Virtual Cross-cultural Teams In Management Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, students often find online intercultural communication challenging during activities such as group work (Mittelmeier et al, 2018). Other concerns have been raised about the lack of authentic engagement with international perspectives in online contexts (Ramanau, 2016). Although Leask and Carroll (2011, p. 655) suggested that internationalized activities "must be designed in a way that, because of their very nature, they cannot be completed satisfactorily without a meaningful intercultural interaction," global evidence suggests that this is often far from the case in IaD activities.…”
Section: Further Developing Iad Pedagogiesmentioning
confidence: 99%